Performative archives: montages and remontages in the contemporary documentary of the Southern Cone (Chile, Argentina, Brazil) - Pinto Veas, Ivan Pablo; Lattanzi Vizzolini, Maria Laura (Revista de Historia Social y de las Mentalidades, 2023)
Starting from the so-called “archival turn”, the article proposes the analysis of contemporary documentaries from the southern cone that suggest new approaches to the problem of the representation of the past. From material poetics to anachronistic remontages, these documentaries are characterized by configuring through their operations new modalities of "remounted archive" cinema, moving from a referential, informative and vertical use to a contingent, fallible and open one.
Keywords: Documentaries; Archive; Memory; Performative